CREATIVE COUNSELING (PROOPS) MELALUI PENDEKATAN SFBC (SOLUTION-FOCUSED BRIEF COUNSELING) UNTUK MENINGKATKAN HARGA DIRI (SELF-ESTEEM) SISWA - Andreas Rian Nugroho; Taat Guswantoro (Jurnal Dinamika Pendidikan, 2020)
Self-esteem is the whole method used to evaluate ourselves, where there is a comparison between ideal-self and real-self. Researchers have carried out strategies for developing self-esteem, but research on increasing self-esteem through creative counseling has not been found. The purpose of this study was to find (1) the profile level of students' self-esteem; (2) Description of the effectiveness of Creative Counseling (Proops) through the SFBC (Solution-Focused Brief Counseling) Approach to Increase Students' Self-Esteem. Keywords: creative counseling, self-esteem, sfbc, student